Brain-Computer Interface Research A State-of-the-Art Summary -2 - Guger, Christoph; Allison, Brendan; Leuthardt, E.C (Biosystems & Biorobotics, 2014)
This book reports on the latest research and developments in the field of brain-computer interfaces (BCIs). It introduces ten outstanding and innovative BCI projects, nominated as finalists for the BCI award 2012 by a jury of established researchers, and discusses how each of the nominated projects reflects general worldwide trends in BCI development. At the core of the book, nine of these ten projects are described in detailed individual chapters. These include a focused introduction to each project, an easy to grasp description of the methods, and a timely report on the most recent developments achieved since the submission to the award. Hence, this book provides a cutting-edge overview of the newest BCI research trends, from leading experts, in an easy to read format supported by explanatory pictures, graphs, and figures.    .